Nanobubble technology in anaerobic digestion: A review. (June 2021) - Chuenchart, Wachiranon; Karki, Renisha; Shitanaka, Ty; Marcelino, Kyle Rafael; Lu, Hui; Khanal, Samir Kumar
Graphical abstract: Highlights: Nanobubble technology has potential to improve the anaerobic digestion process. Underlying mechanisms need to be fully elucidated. Development of process controls is required to facilitate new studies. In-situ nanobubble generation should be explored for industrial applications. Convergence of concepts in anaerobic digestion and nanobubble fields is needed. Abstract: Nanobubble technology has significant potential to improve the anaerobic digestion (AD) process by ameliorating the rate-limiting steps of hydrolysis and methanogenesis, as well as providing process stability by reducing sulfide and volatile fatty acid (VFA) levels. Nanobubbles (NB) can enhance substrate accessibility, digestibility, and enzymatic activity due to their minuscule size, high electrostatic interaction, and ability to generate reactive oxygen species. Air- and O2 -NB can create a microaerobic environment for higher efficiency of the electron transport system, thereby reducing VFAs through enhanced facultative bacterial activity. Additionally, H2 - and CO2 -NB can improve hydrogenotrophic methanogenesis. Recently, several studies have employed NB technology in the AD process. There is, however, a lack of concise, synthesized information on NB applications to the AD process. This review provides an in-depth discussion on the NB-integrated AD process and the putative mechanisms involved. General discussions on other potential applications and future research directions are also provided.